Effectiveness Of Classical Music Therapy And The Use Of Lavender Aromatherapy On Anxiety During Childbirth In Maternity - Nur Sitiyaroh (International Journal of Health and Pharmaceutical (IJHP), 2022)
Anxiety is a feeling of discomfort or excessive fear of a person. Anxiety during childbirth is an inconvenience for the mother giving birth so that there is a fear of her birth. Anxiety can be overcome with non-pharmacological therapies such as classical music and lavender armmatherapy. To determine the effectiveness of classical music therapy and the use of lavender aromatherapy on anxiety during childbirth in women giving birth at Belinda Clinic. This study was conducted in a quasi-experimental one group pre-test and post-test design with a quantitative approach. The sample of this research is the total population of 30 mothers giving birth at Belinda Clinic by accidental sampling. when the research was conducted September, October, November, and December 2019. The results of univariate analysis are the majority of anxiety levels before being given treatment, namely moderate anxiety levels totaling 16 people (53.33%) and after treatment, the majority of mild anxiety levels are 18 people (60%). The results of the bivariate analysis showed that there was a difference before and after the level of anxiety during childbirth using classical music therapy and the use of lavender aromatherapy with a p-value of 0.000 Conclusions and Suggestions: the health sector, especially midwives, to reduce anxiety levels in maternity mothers by using classical music therapy and the use of lavender aromatherapy